Heads of Departments Leadership Styles, Work Climate and Organizational Commitment Enhance the Job Performance of University Lecturers - ZAMIN, SYED ALI; HUSSIN, DR.FAUZI (The journal of contemporary issues in business and government, 2021)
For survival in the environment and increase organizational success it is mandatory for any organization to focus on enhancing employees’ job performance. The main objective of this study was to determine the correlation of leadership styles, work climate and organizational commitment with job performance. The public universities lecturers were selected as population of the study while 339 lecturers were administered as a sample for this study through stratified random sampling technique. Data was collected by using standardized questionnaire through survey method. Statistical Package for Social Sciences (SPSS-25) was adopted to analyse the data according to the proposed hypothesis. It was concluded that the constructs such as; leadership styles, work climate and organizational commitment are the predictor to boostjob performance of lecturers.